Importance of histopathological analysis and molecular genetics in a rare neonatal case of rhabdomyosarcoma. (2nd May 2022) - Gramp, Prudence; Zappala, Tania; Von Schuckmann, Lena; Payton, Diane; Wheller, Laura
Abstract: We present a case of a neonate who presented with multiple cutaneous and subcutaneous nodules, which was found to be metastatic embryonal rhabdomyosarcoma. Rhabdomyosarcoma is a soft tissue malignancy that usually occurs in children aged one to five but is rare in neonates. The histopathological analysis and molecular genetics are important in the classification of subtype and in guiding treatment options and informing prognosis.